2022
DOI: 10.3390/polym14194106
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Bioactivity of Polysaccharides Separated through a (Sequential) Biorefinery Process from Fucus spiralis Brown Macroalgae

Abstract: Marine macroalgae biomass is a valuable renewable resource that can be used for the development of bioeconomy through the valorisation of valuable compounds. The aim of the current study is separate macroalgal polysaccharides with bioactive properties from brown macroalgae Fucus spiralis based on a designed biocascading biorefinery approach. Thus, we applied an integrated processing method for the separation of fucoidan and alginate, in addition to characterization through IR spectroscopy and 1H NMR. The bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 120 publications
0
0
0
Order By: Relevance
“…As shown in Figure 4, the FTIR and NMR spectra of the extracted fucoidan exhibit notable differences in absorption patterns to those of fucoidans extracted from Sargassum cristaefolium, Sargassum sp., Turbinaria sp., Fucus vesiculosus, and Padina sp. [32][33][34][35]. This confirmed that fucoidan composition is influenced by the extraction method and algal species.…”
Section: Discussionsupporting
confidence: 69%
“…As shown in Figure 4, the FTIR and NMR spectra of the extracted fucoidan exhibit notable differences in absorption patterns to those of fucoidans extracted from Sargassum cristaefolium, Sargassum sp., Turbinaria sp., Fucus vesiculosus, and Padina sp. [32][33][34][35]. This confirmed that fucoidan composition is influenced by the extraction method and algal species.…”
Section: Discussionsupporting
confidence: 69%